1977
DOI: 10.1111/j.1464-410x.1977.tb04146.x
|View full text |Cite
|
Sign up to set email alerts
|

Parameatal Urethral Cysts: a Review of 6 Cases

Abstract: 6 cases of parameatal urethral cysts are reported in 3 males and 3 females. The condition is considered to be rare. The aetiology is thought to be obstruction of the para-urethral ducts possibly due to infection. The treatment of choice is complete excision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
5

Year Published

1982
1982
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 2 publications
0
16
0
5
Order By: Relevance
“…[9] Konjenital parameatal kistli olgular bebeklik döneminde tanı-nabilir, ancak idrar projeksiyonunda bozulma ve kitle nedeniyle daha ileri yaşlarda hekime başvururlar. [10] Parameatal kist genellikle asemptomatiktir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…[9] Konjenital parameatal kistli olgular bebeklik döneminde tanı-nabilir, ancak idrar projeksiyonunda bozulma ve kitle nedeniyle daha ileri yaşlarda hekime başvururlar. [10] Parameatal kist genellikle asemptomatiktir.…”
Section: Discussionunclassified
“…Sünnet derisini ayırma sırasında oluşabileceği, infeksiyon gibi nedenlerle paraüretral kanal tıkanıklığının kist oluşumuna yol açtığı savunulmuştur. [7,9,12] Yakın zamanda Soyer ve ark., [13] meme büyüklüğü ve vajinal kanaması olan paraüretral kistli yenidoğan iki kız olgu rapor ettiler. Bu olgular paraüretral kist gelişiminde östrojenlerin rolünü akla getirmiştir.…”
Section: Discussionunclassified
“…Thompson and Lantin indicated that parameatal urethral cysts occurred in the process of delamination or separation of the foreskin from the glans penis, while Yoshida 9 believed that they were caused by occlusions of paraurethral ducts. Hill and colleagues 10 suggested that these obstructions could be caused by infections. Recently, Soyer and colleagues 11 reported two cases of newborns, in whom paraurethral cysts were associated with vaginal bleeding and breast enlargement; these factors showed the possibility of the role of estrogens in their development.…”
Section: Discussionmentioning
confidence: 99%
“…Only 20 parameatal urethral cysts have been reported so far in the literature [Hill and Handley Ashken, 1977], The first report was by Thompson and Lantin [1956]. Most of the patients were males.…”
Section: Introductionmentioning
confidence: 99%